Adulteration Detection Of Stingless Bee Honey Using Untargeted 1h-Nmr Metabolomics In Addressing The Limitation Of Stable Carbon Isotope Ratio Analysis - Yong, Chin Hong (2022)
As stingless bee honey (SBH) is gaining in popularity in the Malaysian market, it is now prone to adulteration. Some studies have found that the nutritional values of SBH may be similar if not more than honey bee honey (HBH), The higher price of SBH as compared to HBH has led to the use of unusual adulterants such as vinegar and even HBH to mimic the unique taste and appearance of SBH. To determine the authenticity of honey in general, the current internationally accepted method used is the Association of Official Analytical Chemists (AOAC) Internal Standard Carbon Isotope Ratio Analysis (ISCIRA) method.